THE LEGAL STATUS OF IN VITRO EMBRYOS - Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Our science has advanced greatly and continues to do so. While being witnesses to this phenomenon, we are not yet ready to fully accept all of its results which can lead to the improvements of our biological structure, or our lives, in other words. There is a wide range of objections aimed at preventing any tests on embryos, deeming such actions as immoral, discriminatory or contrary to nature. However, the question is whether we are actually able to prevent such actions, to prevent obtaining further information that can assist in improving human life, i.e. to prevent future parents from providing the best future possible for their children?